Proposal of a Conceptual Model for Factors Affecting Decisions on Application of Green Practices in Accommodation Establishments - A Case Study in Vietnam - Thao, Nguyen Thi Phuong (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 1 No 2, 2021)
The purpose of this research is to propose a conceptual model for factors affecting decisions on application of green practices in accommodation businesses in Vietnam. Through reviewing and evaluating the content of previous researches, the model will provide an integrated perspective for researchers to experimentally test the relationships between external factors (institutional pressure), internal factors (motivation and environmental attitude of the upper managers) and the adoption of green practices in hospitality businesses. Although the model is expected to contribute to the literature when studying corporate social responsibility, the author suggests that an empirical research should be done to confirm the relationship of the variables in the model or changes (if any) to adapt to the research context in transitional economies such as that of Vietnam.